Achieving Energy Savings by Intelligent Transportation Systems Investments in the Context of Smart Cities - Chen, Yang (World Bank E-Library Archive, 2016)
To further explore the energy efficiency potential of Wuhan and to mainstream ITS and smart transport solutions as a source of achieving energy efficiency using results of this study, a TRACE analysis was also completed as part of this research effort. This analysis focused on the passenger transport sector. Finally, policy recommendations on the major conditions under which ITS investments in the context of smart cities achieve energy savings are summarized in Section 6 with specific implications for cities in the developing countries